Similar Aspects of English and Uzbek Literature - Abdullayeva Visola Sherali qizi (International Journal on Integrated Education, 2022)
The main purpose of the work is to compare the interpretation of the artistic world of childhood in American (Uzbek) and Uzbek literature, the peculiarities and commonalities between them. The analysis of the works of the famous poet and translator G. Gulam "Shum bola", the study of their differences and methodological peculiarities. The world of literature plays an important role in the growth and strengthening of cultural cooperation between nations. The rise of the culture of nations and peoples is inconceivable without literary connections and the constant development of this process.